IMPLEMENTATION OF AN E-COMMERCE BASED ONLINE SALES SYSTEM AT DAPOER LN MSME KUDUS - Saputra, Bayu Angga; Supriyanti, Endang; Listyorini, Tri (Tekmapro, 2025)
This research aims to design and implement an e-commerce based website specifically designed to help Dapoer LN MSME in managing and increasing online product sales, in line with the need to adapt to digital technology to face increasingly fierce market competition. The development process covers all stages, from design to implementation, involving MSME business owners as the main users to ensure the features developed suit their needs. This research methodology uses observation to understand business processes and operational needs, interviews to identify challenges in digital marketing, and literature studies to find the best approach in e-commerce design. This website is designed with various main features for business owners, such as product category features, products, orders, coupons, customer data, customer reviews, and reports, as well as features for customers, such as product features, orders, reviews, and payments. The design focuses on user-friendly interface design, data security, and effective digital marketing strategies to improve customer experience and expand the market. With features that support inventory management and customer data analysis, this website is expected to become a strategic tool to increase competitiveness, reduce operational costs, and encourage the growth of Dapoer LN MSME. This research is limited to feature development without including a financial recording system, making it a complete and efficient solution to support the success of Dapoer LN MSME in facing the challenges of the modern technological era. Keywords: MSME, websites, e-commerce, development, digitalization